PENYELESAIAN PERKARA KUMULASI GUGATAN ITSBAT NIKAH DAN CERAI GUGAT (STUDI KASUS PENGADILAN AGAMA SIDENRENG RAPPANG KELAS II) - Talli, Halim; Fajri, Muhammad; Hermayanti, Riska (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2025)
This study discusses the settlement of cases of cumulative marriage and divorce lawsuits (case study of the Sidenreng Rappang Religious Court Class II). This study aims to find out how the process of settling the cumulative lawsuits for itsbat marriage and divorce lawsuits and how the basic legal considerations used by judges in resolving cases of cumulative lawsuits for itsbat marriage and divorce lawsuits. The type of research used is qualitative research which analyzes qualitative data so that the research is in accordance with the facts on the ground. The approach used is a normative juridical approach with data collection methods, namely documentation and interviews. The results of the study revealed that the process of the accumulation of marriage itsbat and divorce lawsuits at the Sidenreng Rappang Religious Court was broadly resolved in several stages, namely: The process of examining the marriage itsbat case. The mediation process is assisted by the panel of judges. Divorce proceedings. The deliberation meeting of the panel of judges and the reading of the decisions. The judge's consideration in deciding cases of itsbat marriage and divorce is based on the evidence and facts that the panel of judges got.